Pengembangan Produk Cokelat Couverture dengan Penambahan Pangan Fungsional di Desa Randualas Kecamatan Kare Kabupaten Madiun - Achmad Ridwan Ariyantoro; Choiroel Anam; Kawiji Kawiji; S Minardi; Fitriyah Zulfa; Didik Purnomo; Eny Muzayana; Rohmat Priya Atmaja; Clysna Widiatmoko (Universitas Sebelas Maret, 2019)
Title: The Development of Courverture Chocholate Product with Addition of Functional Food in Randualas Village, Kare District, Madiun Regency. Madiun Regency chose cocoa as one of the main commodities which could be developed because it was appropriate with the soil structure on the slopes of the mountains and as a tourist destination. Randualas Village cocoa farmers, Kare Subdistrict, Madiun Regency have a problem that is the selling price of cocoa beans is still low, so it needs to increase the selling value by making processed products from cocoa beans into food products such as chocolate couverture. Besides that, the development of chocolate-based products needs to be improved with the addition of functional food so that it has benefits for human health. The target of community service was to increase the ability of cocoa farmers to develop couverture chocolate products by adding functional food with soybean flour for increase the income of cocoa farmers. The activities carried out were the socialization, counseling, training and practice of the couverture chocolate production process which includes training on process and packaging of products. The community service resulted in an increase in farmers' knowledge in processing chocolate with the addition of functional food.